Aharonov-Bohm Phase for an Electric Dipole on a Noncommutative Space - Ababekri, Mamut; Anwar, Abduwali; Hekim, Mamatabdulla; Rashidin, Reyima (Frontiers in Physics, 2016)
We study the non-relativistic behavior of a particle with electric dipole moment and interacting with external electromagnetic fields on a noncommutative space(NCS). For a special configuration of the field, we derived the phase of an electric dipole as an application of the AB effect to a system composed of two charges. We find that the quantum phase for electric dipole obtains some correction, and this correction depend on the noncommutative parameter explicitly.